The Influence of Healthy Lifestyle on Willingness to Consume Healthy Food Brands: A Perceived Value Perspective - Elizabeth Emperatriz García-Salirrosas; Jorge Alberto Esponda-Perez; Dany Yudet Millones-Liza; Karla Liliana Haro-Zea; Luiggi Agustin Moreno-Barrera; Ghenkis Amilcar Ezcurra-Zavaleta; Luis Alberto Rivera-Echegaray; Manuel Escobar-Farfan (Foods)
This paper aims to build a predictive model that assesses how a healthy lifestyle affects different dimensions of perceived value (quality, social value, emotional value, and economic value) and how these dimensions impact the willingness to purchase healthy brands. A quantitative, non-experimental, and cross-sectional study was conducted with a sample of 515 participants. A self-administered questionnaire was used, and the data were analyzed using the PLS-SEM method. The findings indicate that a healthy lifestyle positively influences the perception of quality and the social, emotional, and economic value of healthy brands. However, only perceived quality, social value, and emotional value significantly impacted the willingness to purchase, while economic value did not show a relevant effect. It is concluded that a healthy lifestyle is a determining factor in the perception of the value of healthy foods, which reinforces the purchase intention, except for economic value. These findings suggest that companies should prioritize strategies that reinforce the quality and emotional and social connections of their products to encourage the consumption of healthy brands. This study contributes theoretically to the perceived value model in emerging markets and provides practical implications for designing more effective marketing strategies in the Peruvian context.